Sustainable Livestock Development Strategy Through Artificial Insemination Evaluation In Nganjuk - Efi Rokana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2018)
ABSTARCT This study aims to obtain the relationship between the breed and parity of fcattle against the success rate of AI in District Rejoso Nganjuk and to produce sustainable livestock development strategy through the application of AI technology in District Rejoso Nganjuk. This research conducted for 6 months in the District Rejoso Nganjuk Regency. The material used in this research is frozen semen (straw) from Limousin bull, female cattle as many as 45 cattle in different breed and parity namely Limousin cross, Simental cross, Ongole cross, and Brahman cross. This research method is survey. The research data are secondary data and primary data. The sample is determined by using purposive sampling method. The research variable is the success rate of AI calculated by knowing the value of S/ C (Service per conseption). The data obtained are analyzed descriptively and analytically. Statistical analysis by using logistic regression to determine the relationship between breed and parity with the success of AI. Descriptive analysis is used to explain that Artificial Insemination technology can be applied as one of sustainable livestock development strategy in Rejoso Sub-district of Nganjuk Regency, taking into account ecological, economic, socio-cultural, institutional, and technology and human resource aspects. The Brahman cross regression coefficient is 4,094 (p = 0.004) gives an interpretation that the success rate of 1 straw in the Brahman cross is higher and significantly different than that of the Limousin cross. Ongole cross regression coefficient is 1,628 (p = 0,148) giving interpretation that success rate with 1 straw on Ongole cross is higher but not significantly different compared to Limousin cross. Simental cross coefficient is 3.829 (p = 0.002) gives an interpretation that the success rate with 1 straw in the Simental crossd is higher and significantly different than the Limousin cross. So the results of comparison between four breeds, this success rate of pregnancy with 1 straw in sequence is the Brahman cross, Simental cross, Ongole cross and Limousin cross. Implementation of Artificial Insemination technology is very appropriately applied as one of sustainable breeding cattle breeding strategy in Nganjuk District because it fulfills the principles of relationship among ecological, economic, socio-cultural, institutional / institutional, and technology components. Key word: sustainable development, artificial insemination, service per conseption